Nutritional status of the cauliflower cultivar 'Verona' grown with omission of out added macronutrients - Bianco M.S. (2015)
© 2015 Bianco et al.Knowledge of plant nutritional status allows an understanding of the physiological responses of plants to crop fertilization. A hydroponic experiment evaluated the symptoms of macronutrient deficiency in cauliflower 'Verona' and determined: a) the macronutrient contents of foliar tissues when visual symptoms were observed, b) macronutrients content of foliar and inflorescence tissues at harvest. The effect of nutrient deficiency on inflorescence mass was also evaluated. Nitrogen deficiency caused chlorosis followed by purple color in the old leaves, while P deficiency caused only chlorosis in old leaves. Chlorosis at the edge of old leaves progressing to the center of the leaves was observed with the omission of K, and after was observed necrosis in the chlorotic areas. Ca deficiency caused tip burn in new leaves, while Mg deficiency caused internerval chlorosis in old leaves. The omission of each macronutrient reduced inflorescence dry matter. This deleterious effect was larger for N, P, and K deficiencies, reducing inflorescence dry matter by 87, 49, and 42%, respectively. When the nutrient solutions without N, P, K, Ca, or Mg were supplied to cauliflower plants, the macronutrient contents at harvest were 8.8, 0.6, 3.5, 13.0, and 0.8 g kg-1 in the foliar tissues and 27.3, 2.2, 21.6, 1.1, and 0.7 g kg-1 in the inflorescence tissues, respectively.